HEALTHY EATING CONCEPTS OF SENIORS ATTENDING THE UNIVERSITY OF THIRD AGE - Christiane Ayumi Kuwae (Universidade do Estado do Rio de Janeiro, 2013)
This dissertation reflects upon the concepts of healthy eating habits in the third age, based on the plurality of meanings of what constitutes good nutrition. The term "healthy eating" relates to several similar meanings, but which are not synonymous. Understanding what is good or bad eating habit is something that lies on cultural, historical, psychological and / or nutritional aspects which are not always convergent, have the same rationality, nor the same meaning. The focus of this study, with respect to diet, is on the perspective of socio-anthropological studies, aiming to deepen on the symbolic relations of eating in the third age, whereas the context of modernity represents a scenario from where the concepts of healthy eating are drawn. Just as such concepts are affected by the current perspectives of aging. We point out that the concept of third age is an aging proposal aligned with the values ​​of today's society, such as time and body productivity, and which finds in the Universities of Third Age a prime space for (re) production. According to our study, the concepts of healthy eating among the elderly are connected to the values ​​of the modern world, including the practicality and appreciation of body care. Meanwhile, these concepts represent the stresses of urban diet, such as the need and mistrust related to the food industry, and the different manners of eating. We have noted that the elderly seek for nutritional rules on how to eat within the context of modern world and the needs of an aging body. Finally, the plurality of meanings on how to eat healthy in the third age, examined in this study, points to the complexity of studies on eating habits, regarding the dynamism of the construction of meanings and concepts of what is a good diet these days.